Cultivating a Culture of Innovation Nurturing Entrepreneurial Spirit and Startup Mindset in Engineering Education - Goli, Gurunadham; Babu, D Ramesh (Journal of Engineering Education Transformations, 2025)
In today's rapidly evolving world, the role of engineers has transcended conventional boundaries, requiring not just technical proficiency, but also the ability to think creatively, adapt swiftly, and translate concepts into practical solutions. This article underscores the significance of instilling a culture of innovation, entrepreneurial spirit, and startup mindset within engineering education. It emphasizes the need for these qualities in light of the dynamic nature of engineering challenges. The evolving educational landscape must instill students with the capacity to tackle future complexities. This article accentuates the essence of entrepreneurial thinking and startup-oriented approaches without resorting to quantitative or qualitative analysis. It explores how integrating entrepreneurial concepts into engineering education can foster inventiveness, interdisciplinary cooperation, and industry preparedness. Furthermore, it addresses the potential hurdles in implementing such an approach. In essence, this article asserts that by cultivating entrepreneurship, educators equip engineering students to emerge as inventive problem solvers and catalysts for societal advancement.